Strategic Integration of Second-Life Batteries: Incentive Mechanisms for Boosting Community Energy Self-Consumption - Terkes, Musa; Demirci, Alpaslan; Ozturk, Zafer; Cali, Umit (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
Energy storage systems (ESS) can provide flexible and reliable energy management due to the rapid development of distributed renewable energy systems (RES). Second-life batteries (SLB) can overcome the environmental concerns and high investment costs related to fresh battery production. However, the integration of storage-based RES poses several challenges regarding optimal control strategy, power quality, and participation in the energy market. These questions can be listed as follows: Which economic strategy favors the integration of SLB-based storage? Which policy among the individual financial strategies can further improve the decision criteria in favor of the prosumer without causing power quality issues? Which measures should be taken, and which hybrid incentive mechanism should be proposed to complement the lacking feasibility performance of individual economic plans? To fill this gap, this study evaluates the feasibility of different incentive policies, individual or hybrid, considering prosumers' self-consumption. Moreover, sensitivity analyses consider carbon tax (CT) and investment subsidies (INVs) for prosumers. The results show that the high purchase price of SLBs can be eliminated, provided that the 20% above investment subsidy for prosumers purchasing cheaper electricity. Adopting 1$/t CT could reduce carbon emissions by up to 1.9 t/yr, and a 1% total investment subsidy could increase photovoltaic panel (PV) capacity by 11.28 kW. The prosumer benefit under net metering can be maximized if the total INV and CT are managed at 20% and 40$/t in Turkiye. This study encourages investors and prosumers to sensibly plan a shared ESS in individual and hybrid incentive mechanisms.
Keywords: Investment; Costs; Economics; Government policies; Production; Electricity; Carbon tax; Renewable energy sources; Energy storage; Energy management; Battery management systems; Life testing; feed-in tariff; investment subsidy rate; net billing; net metering; renewable energy; FEED-IN-TARIFF; POWER-SYSTEM; ELECTRICITY-GENERATION; MODEL; COST; EXPANSION; CAPACITY; IMPACTS; Computer Science; Engineering; Telecommunications